Detecting Canada : essays on Canadian crime fiction, television, and film - Rose, Marilyn J; Sloniowski, Jeannette, 1946- (Wilfrid Laurier University Press, 2014)
This book-length study of crime writing in Canada, Detecting Canada, contains thirteen essays on many of Canada's most popular crime writers, including Peter Robinson, Giles Blunt, Gail Bowen, Thomas King, Michael Slade, Margaret Atwood, and Anthony Bidulka. Genres examined range from the well-loved police procedural and the amateur sleuth to those less well known, such as anti-detection and contemporary noir novels. The book looks critically at the esteemed sixties' television show Wojeck, as well as the more recent series Da Vinci's Inquest, Da Vinci's City Hall, and Intelligence, and the controversial Durham County, a critically acclaimed but violent television series that ran successfully in both Canada and the United States. The essays in Detecting Canada look at texts from a variety of perspectives, including postcolonial studies, gender and queer studies, feminist studies, Indigenous studies, and critical race and class studies. Crime fiction, enjoyed by so many around the world, speaks to all of us about justice, citizenship, and important social issues in an uncertain world.
Keywords: Detective and mystery stories, Canadian -- History and criticism.; Crime on television -- History and criticism.; Roman policier canadien -- Histoire et critique.; Criminalité à la télévision -- Histoire et critique.; LITERARY CRITICISM -- American -- General.; Crime on television; Detective and mystery stories, Canadian; .; Alias Grace.; Anthony Bidulka.; Australian detective fiction.; Beryl Langer.; Canadian Psycho.; DaVinci's Inquest.; Durham County.; Eric Wright.; Gail Bowen.; Giles Blunt.; Gothic RCMP.; Howard Engel.; Indigenous detective fiction.; Jennifer Andrews.; Manina Jones.; Margaret Atwood.; Peter Robinson.; Thumps DreadfulWater.; Wojeck.; canadian detectives.; canadian mystery writers.; canadian tv detectives.; detective fiction.; mystery.; Criticism, interpretation, etc.; Detective and mystery stories, Canadian.